The Life of Chariton the Confessor (September 28) by Symeon the Metaphrast asa Source for the Life of John the New of Suceava (June 2) by Gregory Tsamblak - Temčinas, Sergejus (Slavistica Vilnensis, 2025)
The article demonstrates that while writing the Life of the martyr John the New of Suceava, the first national Moldavian saint, the internationally known prolific Bulgarian author Gregory Tsam- blak must have used one of several existing Church Slavonic versions of the Byzantine Life of the venerable Chariton the Confessor, written by Simeon the Metaphrast, which is quite different it its plot. It is manifested in a quite extensive verbatim quotation of its incipit in the opening sentence of the text. Tsamblak must have consulted the Byzantine Life in its East Slavonic version, as the collation pre- sented in the article evidently shows, since only a weak connection with the South Slavonic version can be traced. The fact that Tsamblak used Symeon’s hagiography in the Church Slavonic translation and not in the Greek original excludes the theoretical possibility that the Life of John the New was origi- nally written in Greek by a different (anonymous) author, as it is sometimes assumed. It is explained by Gregory Tsamblak’s appreciation of the Jerusalem Typikon, quite new in the early 15th-century Moldova, while creating the new national Moldavian church cult of John the New of Suceava, since the ecclesiastic tradition features Chariton the Confessor as the earliest “creator” of the Jerusalem Typikon.
Keywords: Gregory Tsamblak; Symeon the Metaphrast; John the New of Suceava; Chariton the Confessor; hagiography; intertextuality; Byzantine-Slavonic cultural relations